Tumor necrosis factors blocking agents: analogies and differences - Benucci, M.; Saviola, G.; Manfredi, et al., M. (Acta Biomedica Atenei Parmensis, 2012)
Five anti-TNF agents, infliximab, adalimumab, etanercept, golimumab and certolizumab pegol are approved worldwide for the treatment of RA. Anti-TNF agents, bind to and neutralize soluble TNF-α, but exert different effects on transmembrane TNF-α-expressing cells (TNF-α-producing cells). Differences on affinity and avidity for soluble and transmembrane TNF-α were showed. Different activity on cells apoptosis, Complement-dependent cytotoxicity (CDC) antibody dependent cell-mediated cytotoxicity (ACDC) were described. Some dramatic changes in gene expression were seen with all the anti-TNFs. Reviewing the biology of transmembrane TNF-α and its interaction with anti-TNF agents will contribute to understanding the bases of differential clinical efficacy of these promising treatment modalities.